2015
DOI: 10.2174/1874325001509010015
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications Following Cemented Modular Hip Hemiarthroplasty

Abstract: Introduction : Hemiarthroplasty is the recommended treatment for displaced, intracapsular, femoral neck fractures. This study aimed to evaluate the early complications following insertion of the JRI Furlong cemented hemiarthroplasty, a contemporary, modular, double tapered, polished prosthesis.Method : A series of 459 consecutive patients (May 2006 - June 2009) treated with a JRI hemiarthroplasty with a minimum of one-year (1-4years) follow-up were evaluated. Data collected retrospectively from clinical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The anatomical stem design of the Lubinus sp II stem is reported to have less periprosthetic fractures than wedge-type stems when using cemented hemiendoprosthesis in femoral neck fracture patients (34). The present rate of intraoperative fractures of 0.8% resembled the rates reported in previous studies (range, 0.8–3.7%) (13, 15, 35). Some of these studies performed both cemented and uncemented hemiarthroplasties, which may in part explain the higher rate of iatrogenic fractures.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The anatomical stem design of the Lubinus sp II stem is reported to have less periprosthetic fractures than wedge-type stems when using cemented hemiendoprosthesis in femoral neck fracture patients (34). The present rate of intraoperative fractures of 0.8% resembled the rates reported in previous studies (range, 0.8–3.7%) (13, 15, 35). Some of these studies performed both cemented and uncemented hemiarthroplasties, which may in part explain the higher rate of iatrogenic fractures.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we report the complications associated with the use of cemented, modular, unipolar HA (Lubinus sp II) and the posterior approach for femoral neck fractures over 8-year follow-up. Given the challenges presented by the patient material, our level of complications is comparable with previous studies (810, 1315, 19).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…There were no major postoperative complications like wound infection and other. Sullivan et al [17] found 3.7% periprosthetic fracture Following Modular Hip Hemiarthroplasty out of 429 patients. Balan et al [10] found no periprosthetic fracture out of 30 patient treated with modular bipolar prosthesis.…”
Section: Discussionmentioning
confidence: 98%